2011
DOI: 10.1016/j.jadohealth.2010.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Parent–Youth Communication and Concordance Between Parents and Adolescents on Reported Engagement in Social Relationships and Sexually Intimate Behaviors in Hanoi and Khanh Hoa Province, Vietnam

Abstract: Corresponding Author: Linda M. Kaljee, Ph.D., Associate Professor, Wayne State University, Pediatric Prevention Research Center, Hutzel Building, Suite W534, 4707 St. Antoine, Detroit, MI, 48201, Phone: 301 873-1203, Fax: 313 745-4993, lkaljee@med.wayne.edu. Publisher's Disclaimer: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
2
16
1
Order By: Relevance
“… 30 Some people even believe that sexuality and relationships are not appropriate for adolescents and young adults because education must be prioritized. 31 However, this may lead to a lack of essential knowledge about sexual health. In the context of Vietnam, those between 20 and 29 years old are more likely than others to be in a romantic relationship, become sexually active, and care about sexual health.…”
Section: Discussionmentioning
confidence: 99%
“… 30 Some people even believe that sexuality and relationships are not appropriate for adolescents and young adults because education must be prioritized. 31 However, this may lead to a lack of essential knowledge about sexual health. In the context of Vietnam, those between 20 and 29 years old are more likely than others to be in a romantic relationship, become sexually active, and care about sexual health.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported that parents are reluctant and embarrassed to discuss sexual health issues with both sons and daughters, and often believe that topics regarding sexuality, pregnancy, and contraception are inappropriate for adolescents (Kaljee et al, ). The findings of this study are similar to these reported by Trinh et al (), who found that mothers felt embarrassment when talking about condom use with sons.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are different from a previous study among students in high school in Taiwan stating that parental influence, as a whole, is more important than peer influence [29] .This implied a change in the role of parents regarding to smoking initiation and cessation of youths. One reason could be that parents have low levels of communication with their adolescents [30] . Moreover, our study also highlighted the co-occurrence of smoking and alcohol drinking and supported the negative association between alcohol drinking and successful smoking cessation.…”
Section: Discussionmentioning
confidence: 99%